STEM application in miniature bridge making can sharpen children's critical thinking patterns - Agustin, Indah Wahyu; Happy, Nurina; Prayito, Muhammad; Hidayah, Miftahul (Universitas Sarjanawiyata Tamansiswa, 2024)
To improve the skills required for students in the 21st century, such as basic skills, competencies, and character, mathematical literacy is one of the critical factors. With the application of STEM, students are expected to be able to think critically so that they can improve their mathematical literacy skills. This research used a descriptive qualitative method with subjects aged 3–9 years in Joho Village, D.I. Yogyakarta, Indonesia. In this study, data was collected using three methods: observation, interview, and documentation. The instruments used include a critical thinking scale, an observation guide, and an interview guide. The results obtained from this study indicate that applying STEM can hone students' critical thinking skills. Two classifications were obtained by applying STEM, namely groups with high and average levels of critical thinking. Students can identify given problems, formulate the core of the problem, provide solutions based on a problem, draw conclusions, and evaluate relevant arguments for solving a problem. Thus, research is expected to provide a strong foundation for applying STEM-based learning to enrich students' mathematical learning experiences and prepare them for future challenges in the age of globalization towards Indonesia in 2045.